The Implementation of Balanced Scorecard in Optimizing Company Performance Through Four Main Perspectives - Suwandi, Disvita Gladis; Aris, Muhammad Abdul (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
The purpose of this study is to investigate how the four primary perspectives of the Balanced Scorecard financial, customer, internal business process, and learning and growth affect the performance of manufacturing companies in the transportation subsector that are listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. Utilizing secondary data from corporate annual reports, a quantitative research methodology was applied. Net Profit Margin, Sales Growth, Operating Profit, and Net Income per Employee were the independent variables, while Return on Assets (ROA) was used to measure the dependent variable, or corporate performance. To evaluate the hypotheses, multiple linear regression analysis was employed. The findings show that ROA is significantly positively impacted by Net Profit Margin and Net Income per Employee, whereas Sales Growth and Operating Profit do not show a significant impact, 92.5% of the variation in business performance can be explained by the model. These findings suggest that profitability and employee productivity are crucial drivers of financial performance. The study contributes to the literature by demonstrating the strategic relevance of the Balanced Scorecard framework in the transportation manufacturing sector and recommends expanding future research with broader variables and sectoral comparisons.